The meaning of work for tutors in distance education - Y. NEVES; H. A. IRIGARAY; J. LIEDKE (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The purpose of this study is to contribute new information to the ongoing debate over the nature of labor and its various forms. Studies examining the significance of work in various contexts, such as the various forms of employment contracts, have yielded varying results. But we still need to find out how DE tutors find fulfillment in their work.Method: Thirty distance education instructors at a university were interviewed for this study, which used a qualitative research approach. Discussion analysis was applied to the transcribed interviews. E. M. Morin’s categories were used to analyze the information gleaned from those interviews (2001). In addition, we noted the emergence of new categories from the interviewees’ responses.Findings: Work, as defined by the tutor in this study, falls into a number of the same broad categories identified by E. M. Morin (2001). It was found, for example, that many people who work as tutors in distance education do not initially set out to become tutors because they believe that tutors are looked down upon. Furthermore, the interviewees lacked a sense of community due to the institution’s high unemployment rate.Implications/Novel Contribution: Academic discussions and debates can benefit from studies that examine what it means to be a distance education tutor and from studies that explore whether the new categories identified in this research are present in other types of educational institutions.